Dietary fibre intake of pregnant women attending general practices in southern Brazil – The ECCAGE Study - Buss, Caroline; Nunes, Maria Angélica; Camey, Suzi; Manzolli, Patricia; Soares, Rafael Marques; Drehmer, Michele; Giacomello, Andressa; Duncan, Bruce Bartholow; Schmidt, Maria Inês (Public health nutrition, 2009)
Increase in fibre intake during pregnancy may reduce weight gain, glucose intolerance, dyslipidaemia, pre-eclampsia and constipation. Few studies have evaluated adequacy of fibre intake during pregnancy. To assess, through an FFQ, the dietary fibre intake of pregnant women receiving prenatal care from general public practices and compare it with current guidelines. Cross-sectional analyses of a pregnancy cohort study (ECCAGE-Study of Food Intake and Eating Behaviour in Pregnancy) conducted in eighteen general practices in southern Brazil, from June 2006 to April 2007. Five hundred and seventy-eight pregnant women with mean (SD) age of 24.9 (6.5) years and mean gestational age of 24.5 (5.8) weeks. The mean energy intake was 11 615 kJ/d (2776 kcal/d). The mean total fibre intake (30.2 g/d) was slightly above the recommended value of 28 g/d (P < 0.001), yet 50% (95% CI 46, 54) of the women failed to meet the recommendation. Whole-grain fibre constituted only 1% of total fibre intake in the cereal group. In adjusted Poisson regression analyses, not meeting the recommendation for fibre intake was associated with alcohol intake (prevalence ratio 1.29; 95% CI 1.11, 1.50) and absence of nutritional guidance (prevalence ratio 1.22; 95% CI 1.05, 1.42) during pregnancy. About half of the pregnant women failed to meet the recommended fibre intake, especially those not reporting nutritional guidance during pregnancy. For most women, whole-grain cereal intake was absent or trivial. Taken together, our data indicate the need, at least in this setting, for greater nutritional education in prenatal care.